2017
DOI: 10.1037/xhp0000369
|View full text |Cite
|
Sign up to set email alerts
|

Implicit spatial-numerical associations: Negative numbers and the role of counting direction.

Abstract: It has been debated whether negative number concepts are cognitively represented on the same mental number line as positive number concepts. The present study reviews this debate and identifies limitations of previous studies. A method with nonspatial stimuli and responses is applied to overcome these limitations and to document a systematic implicit association of negative numbers with left space, thus indicating a leftward extension of the mental number line. Importantly, this result only held for left-to-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 19 publications
4
48
2
Order By: Relevance
“…(A) Average RTs (with SE) to Small magnitude (1,2) and Large magnitude (8,9) providing Go response to a specific numerical magnitude, smaller or larger than 5, produced no RTs advantage in the detection of arrow-targets that were oriented toward the same position that numbers would putatively occupy on a left-to-right oriented MNL. These results provide a clear response to the first problem that we wished to address in the present study and strongly suggest, in agreement with our original theoretical proposal (Aiello et al, 2012;Fattorini et al, 2015;2016), that congruency space-number effects like those described in Fischer and Shaki (2017) depend, as in the case of the SNARC effect, on the concomitant use spatial and numerical codes in the instructions that regulate the performance of Go/NoGo responses rather than on an inherent association between space and number magnitude codes.…”
Section: Figure 3 Experimentssupporting
confidence: 90%
See 4 more Smart Citations
“…(A) Average RTs (with SE) to Small magnitude (1,2) and Large magnitude (8,9) providing Go response to a specific numerical magnitude, smaller or larger than 5, produced no RTs advantage in the detection of arrow-targets that were oriented toward the same position that numbers would putatively occupy on a left-to-right oriented MNL. These results provide a clear response to the first problem that we wished to address in the present study and strongly suggest, in agreement with our original theoretical proposal (Aiello et al, 2012;Fattorini et al, 2015;2016), that congruency space-number effects like those described in Fischer and Shaki (2017) depend, as in the case of the SNARC effect, on the concomitant use spatial and numerical codes in the instructions that regulate the performance of Go/NoGo responses rather than on an inherent association between space and number magnitude codes.…”
Section: Figure 3 Experimentssupporting
confidence: 90%
“…These findings provide support to the hypothesis first advanced in Aiello et al (2012) and re-proposed in Fattorini et al (2015;2016) that the representation of number magnitudes has no inherent left-to-right spatial organization and that this organization is rather temporarily elicited by the use of left/right spatial codes, whether linked to number stimuli through response selection or directly conceptually associated to the same stimuli in the task at hand. In line with our original proposal, Fischer and Shaki (2017) have recently showed that when left/right spatial codes are associated with magnitude codes in the instructions that regulate the release of unimanual Go responses to intermixed numerical targets and pictorial shape-targets pointing to the left or to the right, reaction times (RTs) are faster when in task instructions spatial codes are congruent with the position that numerical targets would occupy on a horizontally oriented MNL. Therefore, an instruction like "push when the number is lower than 5 or the shape points to the left" produces faster RTs than an instruction like "push when the number is lower than 5 or the shape points to the right".…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations